Imperial Fictions : German Literature Before and Beyond the Nation-State - Kontje, Todd Curtis, 1954- (Book collections on Project MUSE., 2018)
"Imperial Fictions explores ways in which writers from late antiquity to the present have imagined communities before and beyond the nation-state. It takes as its point of departure challenges to the discrete nation-state posed by globalization, migration, and European integration today, but then circles back to the beginnings of European history after the fall of the Roman Empire. Unlike nationalist literary historians of the nineteenth century, who sought the tribal roots of an allegedly homogeneous people, this study finds a distant mirror of analogous processes today in the fluid mixtures and movements of peoples. Imperial Fictions argues that it is time to stop thinking about today's multicultural present as a deviation from a culturally monolithic past. We should rather consider the various permutations of "German" identities that have been negotiated within local and imperial contexts from the early Middle Ages to the present"--